Comparison between Vacuum and Forceps Extraction to Neonatal outcome on Prolonged Second Stage of Labor - Syamsuri, Kurdi (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To assess the effectiveness of vacuum and forceps extraction in prolonged second stage in Dr. Mohammad Hoesin Hospital Palembang. Methods: A retrospective study for 5 years (2005-2009) by doing a prognostic test on prolonged second stage of labor. Results: The subject age most commonly ranges from 20 to 35 years (84.8% in the forceps extraction group and 86% in the vacuum group). The common parity was nulliparity (58.1% in the forceps extraction group and 61.58% in the vacuum extraction). In the forceps extraction group, 76.7% scores >7 in the 1 minute APGAR score with the mean score of 7.14±1.62, whilst in the vacuum extraction group, 79.1% scores >7 in the 1 minute APGAR score, with the mean score of 7.16±1.78. And in the forceps extraction group, 94.2 scores >7 in the 5 minute APGAR score with mean score of 8.62±1.11, whilst in the vacuum extraction group, 93% scores >7 in the 5 minute APGAR score with the mean score of 8.65±1.08. It is concluded that there is no significant differences on both 1 and 5 minute APGAR scores (p value is 0.713 and 0.755, respectively). Maternal complication of extended episiotomy and perineal rupture were found more often in forceps extraction, but with no statistically significant difference (p=0.324). Conclusion: There is no difference of effectiveness between forceps extraction and vacuum extraction in the case of prolonged second stage. Physicians are free whether to use the vacuum or foceps according to their own desirability and skill. [Indones J Obstet Gynecol 2012; 36-1:28-31] Keywords: forceps extraction, prolonged second stage, vacuum extraction